Answer:
a) The horizontal asymptote is y = 0
The y-intercept is (0, 9)
b) The horizontal asymptote is y = 0
The y-intercept is (0, 5)
c) The horizontal asymptote is y = 3
The y-intercept is (0, 4)
d) The horizontal asymptote is y = 3
The y-intercept is (0, 4)
e) The horizontal asymptote is y = -1
The y-intercept is (0, 7)
The x-intercept is (-3, 0)
f) The asymptote is y = 2
The y-intercept is (0, 6)
Step-by-step explanation:
a) f(x) = ![3^{x + 2}](https://tex.z-dn.net/?f=3%5E%7Bx%20%2B%202%7D)
The asymptote is given as x → -∞, f(x) =
→ 0
∴ The horizontal asymptote is f(x) = y = 0
The y-intercept is given when x = 0, we get;
f(x) =
= 9
The y-intercept is f(x) = (0, 9)
b) f(x) = ![5^{1 - x}](https://tex.z-dn.net/?f=5%5E%7B1%20%20-%20x%7D)
The asymptote is fx) = 0 as x → ∞
The asymptote is y = 0
Similar to question (1) above, the y-intercept is f(x) =
= 5
The y-intercept is (0, 5)
c) f(x) = 3ˣ + 3
The asymptote is 3ˣ → 0 and f(x) → 3 as x → ∞
The asymptote is y = 3
The y-intercept is f(x) = 3⁰ + 3= 4
The y-intercept is (0, 4)
d) f(x) = 6⁻ˣ + 3
The asymptote is 6⁻ˣ → 0 and f(x) → 3 as x → ∞
The horizontal asymptote is y = 3
The y-intercept is f(x) = 6⁻⁰ + 3 = 4
The y-intercept is (0, 4)
e) f(x) =
- 1
The asymptote is
→ 0 and f(x) → -1 as x → -∞
The horizontal asymptote is y = -1
The y-intercept is f(x) =
- 1 = 7
The y-intercept is (0, 7)
When f(x) = 0,
- 1 = 0
= 1
x + 3 = 0, x = -3
The x-intercept is (-3, 0)
f) ![f(x) = \left (\dfrac{1}{2} \right)^{x - 2} + 2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cleft%20%28%5Cdfrac%7B1%7D%7B2%7D%20%5Cright%29%5E%7Bx%20-%202%7D%20%2B%202)
The asymptote is
→ 0 and f(x) → 2 as x → ∞
The asymptote is y = 2
The y-intercept is f(x) = ![f(0) = \left (\dfrac{1}{2} \right)^{0 - 2} + 2 = 6](https://tex.z-dn.net/?f=f%280%29%20%3D%20%5Cleft%20%28%5Cdfrac%7B1%7D%7B2%7D%20%5Cright%29%5E%7B0%20-%202%7D%20%2B%202%20%3D%206)
The y-intercept is (0, 6)